1981
DOI: 10.1002/jez.1402150308
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic consequences of the extent and disposition of the aqueous intracellular environment

Abstract: Attention is focused on the aqueous compartments of eucaryotic cells (nucleoplasm, cytosol, and interior compartments of cytoplasmic membrane-bound organelles). Previous work on the relationship between cell water content, the physical properties of cell water, and metabolic activity in cysts of the brine shrimp, Artemia is summarized and discussed in that context. A previously proposed general model of the organization of metabolic activity in the aqueous compartments will be summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Even now, water remains elusive in terms of its extent of and disposition within the intracellular environment (20). Just as Wilson (21), in 1925, was unaware of the specific details of the hyaloplasm, present researchers are confronted with trying to understand intracellular compartment organization in terms of the nature of soluble enzymes and the physical properties of the aqueous compartments.…”
mentioning
confidence: 99%
“…Even now, water remains elusive in terms of its extent of and disposition within the intracellular environment (20). Just as Wilson (21), in 1925, was unaware of the specific details of the hyaloplasm, present researchers are confronted with trying to understand intracellular compartment organization in terms of the nature of soluble enzymes and the physical properties of the aqueous compartments.…”
mentioning
confidence: 99%
“…As dehydrative freezing progresses to impinge on restricted water, cell structures can become unstable leading to irreversible injury under some slow cooling conditions [36,45]. A second factor observed at higher cooling rates was related to intracellular ice formation (IIF), with the incidence of injury due to IIF increasing with increasing cooling rate [209].…”
Section: Cryoprotectants: Solutes That Modulate the Liquid Water To Imentioning
confidence: 99%
“…In both cases, microcalorimetric studies have shown that the metabolic rate falls rapidly to no more than a few per cent of the active rate, with an almost complete cessation of carbohydrate metabolism (Hand and Gnaiger, 1988;Glasheen and Hand, 1989). The trigger to hypometabolism in anhydrobiotic embryos seems to be linked to ce11 dehydration and this has led to interesting considerations about the physical state of ce11 water (Clegg, 1981;1984). Recent work has also shown that dehydrated embryos are rich in "compatible" organic solutes, which may help to keep the integrity of macromolecular structures (Glasheen and Hand, 1989).…”
Section: Metabolic Depression: the Brine Shrimp Embryo As A Modelmentioning
confidence: 99%